2017
DOI: 10.24193/subbchem.2017.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Titanium-Dioxide Coatings on Membrane Filtration Properties

Abstract: ABSTRACT. In this study, synthesized TiO2 nanorods and commercial Aeroxide P25 TiO2 nanoparticles were deposited on polyethersulfone (PES) membrane surfaces to compare their photocatalytic activity and effects on membrane surface and filtration properties. The catalysts were deposited on the membrane surface by physical deposition. The effect of the TiO2 amount on the stability of the catalyst layer and its effect on membrane resistance in presence and absence of UV irradiation were investigated. 1.2 mg/cm 2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Additions of TiO 2 nanoparticles increase the stability of adhesive, and the resistance to water sorption and solubility. Other studies revealed that TiO 2 present unique photocatalytic, antibacterial and UVabsorbing properties that recommend as beneficial additives in adhesives and resin composites [8,27].…”
Section: Resultsmentioning
confidence: 99%
“…Additions of TiO 2 nanoparticles increase the stability of adhesive, and the resistance to water sorption and solubility. Other studies revealed that TiO 2 present unique photocatalytic, antibacterial and UVabsorbing properties that recommend as beneficial additives in adhesives and resin composites [8,27].…”
Section: Resultsmentioning
confidence: 99%
“…Physical deposition (5) was used by Kovács et al [69] ( Figure 1c). In this method, the TiO 2 suspension was simply filtered through the membrane in a dead-end stirring cell.…”
Section: Pmrs With Immobilized Photocatalyst (Pmrs With Pms)mentioning
confidence: 99%
“…SEM images of PMs prepared by (a) dip-coating[65]; (b) electrospinning-hydrothermal synthesis[68]; (c) physical deposition[69]; (d) chemical vapor deposition[58].…”
mentioning
confidence: 99%